Light quality regulates growth and flavonoid content in a widespread forest understorey medicinal species Scutellaria Baicalensis Georgi - Ma, Jingran; Zhang, Jiaxing; Xie, Lulu; Ye, Ji; Zhou, Li; Yu, Dapao; Wang, Qing-Wei (Frontiers in Plant Science, 2024)
IntroductionIntroduction: Light is not only essential for plant photosynthesis and growth, but also acts as a signal to regulate its secondary metabolism. Despite the influence of light quality on the yield and flavonoid compounds in commercial crops is well-documented, its role in regulating wild understorey species, particularly medicine plants whose flavonoid biosynthesis driven by multiple spectral regions of canopy sunlight, is less understood.MethodsTo address it, we conducted a light-quality manipulation experiment on Scutellaria baicalensis Georgi, a widespread understorey medicinal species, with light-emitting diodes (LED). This study included eight treatments: UV-A (UV-A radiation), CK (control group), Green (monochromatic green light), and different combinations of blue and red light (R0B4: monochromatic blue light; R1B3: 25% Red+75% Blue light; R1B1: 50% Red+50% Blue light; R3B1: 75% Red+25% Blue light; R4B0: monochromatic red light).ResultsOur results showed that light quality significantly drove morphology, biomass accumulation, and flavonoids biosynthesis in S. baicalensis. R0B4 treatment promoted growth and flavonoids accumulation, including baicalin, and wogonoside concentrations. In contrast, UV-A radiation and green light negatively impacted these parameters compared to CK treatment. Interestingly, plant biomass and flavonoid concentrations were lower in R1B3, R1B1 and R3B1 treatments compared to monochromatic blue or red light.DiscussionOur study found that red light may antagonize blue light-stimulated growth and flavonoids accumulation, indicating a complex crosstalk between photoreceptors. These findings highlight the importance of blue light for optimizing the yield and quality of S. baicalensis in the understorey cultivation. It provides practice suggestion for the efficient management and sustainable cultivation of understorey medicinal plants.